DYNAMIC CHARACTERISTIC RESEARCH ON THE MINE SCRAPER CONVEYOR UNDER FAILURE LOAD - MAO Jun; XIE ChunXue; SUN JiuMeng; AN HuiDong; XIE Miao; WANG Tao (Jixie qiangdu)
Scraper conveyor is always working in complex and poor working environment. It will cause the longitudinal vibration of chains when the scraper group goes on material dragged by the chains,and the fault of seizing the chains caused by a sudden increase in material,foreign body stuck or other factors. Discrete the chain transmission system and establish the system dynamics model of the chain based on Kelvin-Vogit model through the finite element method. Determine the stiffness coefficient of the scraper chain combined with the theoretical calculation and actual measurement data. Carry out the numerical simulation on the fault condition of seizing the chains through the numerical simulation software. Obtain the speed change and tension distribution rules of the chain on the different seizing position. Finally,it is found that the experiment data and the simulation results are basically consistent compared experiment data with simulation results.